Pelatihan Analisis Data Pada Karyawan PT. Resmar Hartana Dalam Era Industri 4.0 - Baringin Sianipar; Ifanlius Nduru; Juanda Tampubolon (Universitas Kristen Indonesia Toraja, 2023)
The role of ICT (Information and Communication Technology) is needed by employees as a provision for them to face the changes and demands of the times in the Industrial Revolution 4.0 era. Operating a computer is a part of hard skills, employees need to have skills in operating programs found in Windows and the program most frequently used is Microsoft Excel. However, to achieve this, companies must overcome several obstacles, such as a lack of quality competence to develop and manage, analyze various high-tech systems Workers who have the competence and skills will be accepted in the world of work in the industrial era 4.0. The output target of this dedication is in the form of training services in the form of information for students about data processing, calculation and data management using the Microsoft Excel application. The method of implementing the activities used is the offline training, discussion, and question and answer method. The results of implementing this community service activity are providing an understanding of the use of the Microsoft Excel application for preparing financial reports and improving the hard skills of Pt employees. Resmar Hartana